45 Simulation using a variety of learning, teaching and assessment strategies: developing competence for professional practice. (17th November 2016) - Edwards, S; Crouchman, CM; Hudgell, L; McCormack, S; Roadnight, S; Sinniah, V
Abstract : This paper relates to the use of simulation with the addition of a variety of technologies, learning, teaching and assessment strategies and won the Guardian teaching excellence category award in March 2016. The project attempted to provide the very best student experience, empowering, supporting and engaging students in learning. The project engaged in simulation activities in partnership with other Faculties within the university and outside, and links to the political imperative to improve the education of the health and social care sector by: Incorporating 'real life' clinical practice profiles to impact on learning, using students' own stories, leading simulations, and setting their own criteria for success. Using both medium and high fidelity equipment giving students immediate feedback on their performance to realise their mistakes but know these will not compromise the patient. Including a variety of moulage with simulation, to add and enhance the authenticity and uses everyday materials for sustainability. Students are able to really inspect the moulage, and decide appropriate assessment, interventions and report their findings. Developing 'live' simulations using actors, service users and students as patients, to take the role of patients, doctors, relatives, bystanders, and helpers. This provides students with the opportunity to think critically, make decisions and develop reflection-in-action skills. Incorporating into simulation innovative assessment strategies, e.g. the use of self- and peer-assessment, videos, debrief and capstone transformative assessment. Paying attention to detail and including relevant paperwork at the end of the bed and bedside accessories to make the ward set up look realistic. The paper is based on a group of teachers', and simulation supervisor's work in the creative and innovative use of simulation, demonstrating the importance of the role of teachers when engaging in conveying, inspiring and developing students' skills.